Frustrated Ambitions: Teacher Associations and Segregated Schooling in the Transvaal, c.1920-1956 - Mayet, Fathima Zahra Ebrahim; Sparks, Stephen (South African Historical Journal, 2024)
This article draws attention to the fact that Indian and Coloured teacher associations in the Transvaal made persistent demands for greater racial segregation in schools (of teaching staff and learners) from the 1930s into the 1950s. This was at a time when the Transvaal Education Department was unable to implement anything approaching meaningful segregation of schooling amongst Indians and Coloureds. The context in which these demands for segregated schooling were made is important to understand: decades of frustrated ambition in an educational system which restricted the training, credentialling, and appointment of teachers according to hardening South African racial hierarchies. Ironically, enforcing greater racial segregation in schooling, especially with regard to teachers and principals, would create space for a rising new class of professionals, displacing white staff and allowing black, Indian, and Coloured teachers to achieve greater upward social mobility. An important justification for making this shift happen was the necessity of expelling white teachers and the associated idea of the benefits of being taught by cultural insiders.